Performance improvement of on-off-keying free-space optical transmission systems by a co-propagating reference continuous wave light - Wang, Zixiong (2013)
In this paper, we analytically investigate an optical signal detection scheme to mitigate the scintillation effect with the assistance of a co-propagating reference continuous wave (CW) light. Using the correlation coefficient between the intensities of the data light and the reference CW light, we mathematically derive their joint intensity distributions under two widely used atmospheric turbulence channel models, namely log-normal distributed channel model and Gamma-Gamma distributed channel model, respectively. We also carry out the Monte-Carlo (MC) simulation and show that theoretical results agree with simulation results well. Our analytical results reveal that when the correlation coefficient is 0.99, the power reductions to achieve BER of 10−3 are 12.3 dB and 20.4 dB under moderate and strong atmospheric turbulence conditions (i.e., Rytov variances of 1.0 and 4.0), respectively. In addition, the feasibility of the scheme applied to wavelength-division-multiplexed (WDM) free-space-optical (FSO) transmission systems is also investigated, where only a single reference CW light could be used to mitigate the scintillation effects on all WDM channels.